DISTRIBUIÇÃO DE METAIS PESADOS NOS SEDIMENTOS DE FUNDO DOS RIOS CACERIBU E GUAXINDIBA, AFLUENTES DA BAÍA DE GUANABARA – RIO DE JANEIRO, BRASIL - Porto, Liliane Jucá Lemos da Silva; Almeida, Cícera Neysi de; Dezotti, Márcia Walquiria de Carvalho; Corrêa, José Augusto Martins; Faial, Kelson do Carmo Freitas; Faial, Kleber Raimundo Freitas (Geochimica Brasiliensis, 2015)
The Caceribu e Guaxindiba Rivers are two important tributaries of Guanabara Bay – RJ. Both are included in two protection environmental area and they are passive from sources and intense differences. The present work had objective to evaluate the heavy metal concentrations (Cu, Cd, Pb, Ni, Mn, Zn e Cr) in bottom sediments fraction from Caceribu and Guaxindiba rivers. For it, were realizes following analyses: Mineralogy, Total concentration heavy metal, organic matter in sediments and sequential extraction of heavy metals, method reported by Tessier and others (1979). Mineralogical analysis shows that the sediments are composed mainly of quartz, microcline and muscovite with several small, albite, gipsite and clay minerals (smectite and kaolinite). In the Guaxindiba River the mineralogy was similar microcline, muscovite, albite and gipsite, with intercalation of hematite. With the exception of Mn, all heavy metals analyzed in sediments of Guaxindiba River showed total concentration heavy metal higher than in the Caceribu River. The organic matter presents in sediments of Caceribu River ranged from 0,20 – 3,29 % and Guaxindiba River ranged from 1,93 – 21,60%. In Caceribu River the two fraction dominating were S4 (organic) Cu 69,13% Cd 86,56% e Pb 46,88% and S5 (residu al) Mn 39,25% Zn 26,80% and Cr 73,50%. With the exception of Zn, all elements following the same tendency that the Guaxindiba River: S4 fraction Cu 44,80%, Cd 88,99%, Ni 26,59% Pb 57,59% Cr 71,69% and S5 fraction Mn 28,72%. Keywords: sediment, heavy metal, sequential extraction, Rio de Janeiro